AB0049 Human Type 1 Innate Lymphoid Cells Accumulate in the Inflamed Synovium in Spondyloarthritis. (9th June 2015) - Yeremenko, N.; Noordenbos, T.; Blijdorp, I.; Hreggvidsdottir, H.; Germar, K.; Bernink, J.H.; Spits, H.; Baeten, D.
Abstract : Background: Spondyloarthritis (SpA) is a major form of chronic inflammatory arthritis characterized by inflammation of axial and peripheral joints and by pathologic new bone formation leading to ankylosis. Consistent genetic, experimental, and clinical evidence indicates that IL-23/IL-17 immune axis plays a pivotal role in the pathophysiology SpA. It remains, however, unknown which IL-23 responsive cells are the major cellular source of IL-17 in SpA. Innate lymphoid cells (ILCs) are an emerging family of innate immune cells that produce various cytokines, including IL-17 and IL-22, and play critical roles in regulation of inflammation and tissue remodeling. Objectives: In this study we investigated the presence and phenotype of ILCs in the peripheral blood and inflamed peripheral joints of patients with SpA. Methods: Paired peripheral blood (PB), synovial fluid (SF) and synovial tissue (ST) were obtained from SpA patients with actively inflamed knee joints. ILCs (lineage negative, CD45 + CD127 + CD161 + ) were analysed by flow cytometry. Results: ILCs were present in all three compartments of patients with SpA. Analysis of ST revealed a significantly increased frequency of total ILCs in the joint compared with PB ((median (IQR) 0.37 (0.12-1.12)% of the lymphocyte population in ST versus 0.06 (0.04-0.09) % in PB, p=0.016). Immunophenotyping of ILC subsets showed a statistically significant increase in the frequency of ILC1 (CRTH2 - NKp44 - ckit - ) in ST (37.8%; 74.43-20.47%) versus SF (7.27%; 0.6-25.1%, p=0.008) and PB (3.45%; 1.45-9.25%, p=0.004). The second most prominent ILCs in the joint were NCR-negative ILC3 (CRTH2 - NKp44 - ckit + ), composing 33.45% (9.54-50.64%) of the total ILCs. NCR-positive ILC3 (CRTH2 - NKp44 + ckit + ) and ILC2 (CRTH2 + ) populations were present in synovium at lower frequencies. Conclusions: We observed an absolute and relative enrichment of both ILC1 and NCR-negative ILC3 in the inflamed ST of patient with spondyloarthritis as compared to PB and SF. As studies in other tissues such as gut and tonsil revealed that these IL-23 responsive ILC subsets can be an important source of IL-17 and /or IL-22 (1, 2), we will further investigate the cytokine production by these synovial ILCs. References: Geremia et al. J Exp Med. 2011 208(6):1127-1133 Bernink et al. Nature Immunology 14(3):221-229 Disclosure of Interest: None declared